Median ages at stages of sexual maturity and excess weight in school children - Luciano, Alexandre P.; Benedet, Jucemar; Abreu, Luiz Carlos de; Valenti, Vitor Engrácia [UNESP]; Almeida, Fernando de Souza; Vasconcelos, Francisco A. G. de; Adami, Fernando (Biomed Central Ltd., 2013)
Background: We aimed to estimate the median ages at specific stages of sexual maturity stratified by excess weight in boys and girls.Materials and method: This was a cross-sectional study made in 2007 in Florianopolis, Brazil, with 2,339 schoolchildren between 8 to 14 years of age (1,107 boys) selected at random in two steps (by region and type of school). The schoolchildren were divided into: i) those with excess weight and ii) those without excess weight, according to the WHO 2007 cut-off points for gender and age. Sexual maturity was self-evaluated by the subjects according to the Tanner sexual development stages, and utilizing median ages for the genitalia, breasts, and pubic hair stages.Results: In the boys with excess weight, precocity was observed in the stages 4 for genitals and pubic hair and 2 for pubic hair, with the values for excess and normal weight. The median ages at the beginning of puberty (stage 2-sexual development) for boys and girls in Florianopolis were 10.8 and 10.3 years, respectively.Conclusion: Excess weight is associated with lower median ages in the sexual maturity stages in boys and girls and that it should be taken into account when evaluating sexual maturity in children and adolescents.
Keywords: Adolescents; Obesity; Early puberty; Scholar children